Transesophageal echocardiographic measurement of coronary sinus blood flow to estimate the adequacy of revascularization in patients undergoing coronary artery bypass graft: a prospective observational study - Parajuli, Santosh Sharma; Adhikari, Rakesh Bahadur (Nepalese Heart Journal, 2024)
Background: Oxygen supply to the myocardium is determined mainly by the amount of the coronary blood flow. Transesophageal echocardiography is being widely used intraoperatively during cardiac surgery. We studied to compare coronary sinus blood flow using Transesophageal echocardiography before and after coronary artery bypass grafting to determine the adequacy of surgical revascularization in a single cardiac centre in Nepal. Methods: Twenty patients scheduled for elective coronary artery bypass grafting were included in this study. After induction of anesthesia according to institutional protocol, a transesophageal echocardiography probe was inserted into patients’ esophagus, and velocity time integral of coronary sinus, coronary sinus diameter, and coronary sinus blood flow per beat at pre-revascularization and post-revascularization periods were recorded. Results: The velocity time integral in the post-revascularization period was significantly higher as compared with the pre-revascularization period (P<0.000). Coronary Sinus diameter in the post-revascularization period was significantly larger as compared with the pre-revascularization period (0.59 vs.0.56 cm) (P<0.000). There was a significant increase in coronary sinus blood flow per beat in the post-revascularization period (4.45±0.66ml) as compared with the pre-revascularization period (4.29±0.65ml) (P<0.000). Conclusion: Transesophageal echocardiography can be used to measure the adequacy of revascularization in CABG patient by measuring the change in real time coronary sinus blood flow before and after revascularization.